Literature Review: Pengaruh Pemakaian Air Sumur Dengan Kejadian Karies Gigi - Purba, As Gaby Clarita; Jelita, Helena; Sampurna Putra, Ravenalla Abdurrahman Al Hakim; Frethernety, Agnes; Lestarisa, Trilianty (Fakultas Kedokteran Universitas Palangka Raya, 2024)
Oral health is the biggest health problem faced by developing countries, namely dental caries. Dental caries is a progressive and cumulative disease of the hard tissues of the teeth and is most prevalent in children aged 5-9 years. Water is the most needed thing in everyday life. Water contains chemical content, one of which is flour content, if abnormal levels can cause dental problems. This study used a systematic review approach with the prism method so that 15 data were found consisting of 10 national journals and 5 international journals. The results of the study found that 11 journals stated a high incidence of caries and 4 journals stated a low incidence of caries based on the DMF-T index and knew the effect of fluorine in well water on the incidence of dental caries.